2012
DOI: 10.1073/pnas.1205598109
|View full text |Cite
|
Sign up to set email alerts
|

NMR imaging of cell phone radiation absorption in brain tissue

Abstract: A method is described for measuring absorbed electromagnetic energy radiated from cell phone antennae into ex vivo brain tissue. NMR images the 3D thermal dynamics inside ex vivo bovine brain tissue and equivalent gel under exposure to power and irradiation time-varying radio frequency (RF) fields. The absorbed RF energy in brain tissue converts into Joule heat and affects the nuclear magnetic shielding and the Larmor precession. The resultant temperature increase is measured by the resonance frequency shift o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Temperature errors of the same magnitude have been demonstrated in various phantom studies [Gultekin and Moeller, 2013; Alon et al, 2015] with slightly higher errors for in vivo studies [Kickhefel et al, 2010]. At the reported standard deviation of the temperature measured here, proper reconstruction was conducted; however, average SAR reconstruction depends on the signal-to-noise of the measurement.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Temperature errors of the same magnitude have been demonstrated in various phantom studies [Gultekin and Moeller, 2013; Alon et al, 2015] with slightly higher errors for in vivo studies [Kickhefel et al, 2010]. At the reported standard deviation of the temperature measured here, proper reconstruction was conducted; however, average SAR reconstruction depends on the signal-to-noise of the measurement.…”
Section: Discussionsupporting
confidence: 56%
“…Okano and Shimoji have shown that RF energy exposure quantification can be conducted by measuring temperature increase due to RF exposure using highly sensitive temperature probes [Okano and Shimoji, 2012]. Gultekin and Moeller [2013] have shown that magnetic resonance (MR) methods can be used to measure temperature increase due to RF energy absorption, where the magnitude of temperature increase was a function of RF power and exposure time in brain equivalent gels and brain tissue [Gultekin and Moeller, 2013]. Recently, high-resolution MR thermal mapping has been utilized for assessment of RF energy absorption from handheld wireless devices [Alon et al, 2015] that output less than 1W of power.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that MRI temperature mapping has been used to quantify RF energy deposition induced by MRI coils (operating at the Larmor frequency) and other antennas , where both RF heating and temperature mapping were conducted inside the bore of the MRI scanner. However, many wireless devices are not MRI‐compatible and therefore cannot be inserted inside the bore of the magnet while maintaining standard operation of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The Federal Communications Commission (FCC) in the United States has set an SAR limit of 1.6 W/kg averaged over 1 g of tissue for partial-body exposure, whereas the Council of the European Union allows a limit of 2.0 W/kg averaged over 10 g of tissue [9] [10]. Extensive cell phone use is known to present the highest radio frequency (RF) exposure to the general public [11].…”
Section: That 24 Ghzmentioning
confidence: 99%